Factors Affecting Employee Work Productivity During the Covid-19 Pandemic - Encep Saefullah; Arta Rusidarma Putra; Tabroni Tabroni (Enrichment : Journal of Management, 2022)
The variables of this research are Leadership (X1), Compensation (X2), Work Discipline (X3), Work Environment (X4), Work Supervision (X5) and Work Productivity (Y). The purpose of this study was to determine the effect of variables X1, X2, X3, X4 and X5 on variable Y partially and simultaneously during the Covid-19 pandemic. This study uses a statement instrument distributed to 68 employees of PT. "X" as the research sample. Data analysis using the PLS method which is an alternative method of analysis with Structural Equation Model (SEM) based on variance. The results of this study indicate that leadership has a positive and significant effect on work productivity, compensation does not have a significant effect on work productivity, work discipline does not have a significant effect on work productivity, the work environment has a negative and significant effect on work productivity and work supervision does not. has a significant effect on work productivity. From the analysis of the factors that affect work productivity, only leadership and work environment have a positive and significant effect on work productivity.